1985
DOI: 10.1021/bi00341a029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for unique homologous peptide sequences around the glycosylated seryl and threonyl residues in polysialoglycoproteins isolated from the unfertilized eggs of the Pacific salmon Oncorhynchus keta

Abstract: Structures of glycopeptides obtained by exhaustive Pronase digestion of high molecular weight (1.7 X 10(5)) salmon egg polysialoglycoprotein have been elucidated. Six principal glycopeptides isolated by gel chromatography and DEAE-Sephadex A-25 chromatography in the absence or presence of borate ion were analyzed for their carbohydrate and amino acid composition, as well as amino acid sequence, and found to be of two distinct types: glycotripeptides, Thr*-Ser*-Glu, and glycotetrapeptides, Thr*-Gly-Pro-Ser, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In order to allocate the glycosylated Ser and Thr residues to the proper positions, we have conducted Pronae digestion of st-H-PSGP(Omi) and st-H-PSGP(Slp) and analyzed the Pronase-derived glycopeptide products. As in the case with st-H-PSGP(rainbow trout) Kitajima et al, 1986; see also Shimamura et al (1985) for glycopeptides derived from Pacific salmon egg H-PSGP], the glycopeptides obtained were essentially assorted into the two distinct groups Thr*-Ser*-Glu and Thr*-Gly-Pro-Ser (data not shown). Consequently, the following structures are determined for VS-GP(Slp) and V8-GP(Omi): Sialidase Digestion of L-PSGP from Fertilized (30-min) Eggs of O. keta (Pacific Salmon) and S. leucomaenis pluvius.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In order to allocate the glycosylated Ser and Thr residues to the proper positions, we have conducted Pronae digestion of st-H-PSGP(Omi) and st-H-PSGP(Slp) and analyzed the Pronase-derived glycopeptide products. As in the case with st-H-PSGP(rainbow trout) Kitajima et al, 1986; see also Shimamura et al (1985) for glycopeptides derived from Pacific salmon egg H-PSGP], the glycopeptides obtained were essentially assorted into the two distinct groups Thr*-Ser*-Glu and Thr*-Gly-Pro-Ser (data not shown). Consequently, the following structures are determined for VS-GP(Slp) and V8-GP(Omi): Sialidase Digestion of L-PSGP from Fertilized (30-min) Eggs of O. keta (Pacific Salmon) and S. leucomaenis pluvius.…”
Section: Resultsmentioning
confidence: 75%
“…^Rilysialoglycoprotein (PSGP)1 was discovered in the unfertilized eggs of rainbow trout by Inoue and Iwasaki (1978). Since then homologous high-molecular-mass PSGPs (H-PSGP; molecular mass ~200 kDa) have also been purified from other salmonid fish eggs (Shimamura et al, 1983(Shimamura et al, , 1984; ; , and thus the widespread distribution of PSGP was demonstrated by examination of eight different species from three genera of Salmonidae. We initiated the structural studies of H-PSGP from different species with initial emphasis on their carbohydrate moieties as these accounted for the major portion of the molecules' mass and vast abundance of sialic acid content (Shimamura et al, 1983(Shimamura et al, , 1985; ; Inoue & Matsumura, 1979Inoue & Iwasaki, 1980;Inoue et al, 1981Iwasaki et al, 1984aIwasaki et al, ,b, 1987Nomoto et al, 1982;Kitajima et al, 1984;Nadano et al, 1986). Our previous studies revealed that (1) H-PSGP is a major component of cortical alveoli Inoue et al, 1987), (2) it undergoes depolymerization (200 to 9 kDa) upon fertilization (Inoue & Inoue, 1986), and (3) the H-PSGP molecule is made up of about 25 tandem repeats of a glycotridecapeptide, and within 5-7 min postfertilization H-PSGP is converted to the repeating unit by a specific protease (Inoue ; Kitajima et al, 1986).…”
mentioning
confidence: 99%